PELINGGIH PADMASANA DALAM EKISTENSI AGAMA HINDU (Bentuk dan Makna) - A.A. Pt. Suari; Gede Arya Krishna Duta Putra Tuboeh (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
Bali island, is an island famous for its natural beauty, culture, and tradition which is very thick with its traditional nuances. then don't be surprised, if the island of Bali is called "Paradise of the World" or "Island of the Gods". besides that the island of Bali is known as "Pulau Seribu Pura". because in almost every corner of the island of Bali, we always find many temples. The temple is a place of worship for Hinduism. In this temple also consists of several Pelinggih or sacred buildings that are intended to worship God and its manifestations. one of the Pelinggih or sacred buildings that is most commonly found in the Temple is Pelinggih Padmasana. This pelinggih has a shape that rises high with the top shaped like a throne. by Hinduism, this pelinggih is dedicated to worshiping Ida Sang Hyang Widhi Wasa as God Almighty in the Hindu religious beliefs themselves. besides that in this pelinggih, there are also various kinds of carvings, sculptures, and reliefs which are full of symbols and meanings of a life in the world.